Pro-Kantin: Digital Entrepreneurship Innovation Through A Pre-Order System For The Campus Canteen Ecosystem - Sabina Rustam; Marsiani Ilham; Anita Triyana (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
Long queues at campus canteens often reduce the efficiency of students’ and lecturers’ daily activities, leading to wasted time and decreased productivity. This condition reflects a broader research problem, namely, the lack of innovative solutions to support efficient and modernized campus ecosystems. The main purpose of this study is to design and analyze PRO-KANTIN (Pre-Order Orchestrated Canteen) as a form of digital entrepreneurial innovation that addresses the inefficiency of conventional canteen services. To achieve this objective, the study employed a descriptive qualitative methodology through a case study approach within a higher education environment. Data were collected through observation of student and lecturer behavior at campus canteens, interviews with canteen managers, and analysis of entrepreneurial business models related to digital platforms. The results indicate that the implementation of PRO-KANTIN significantly improves service efficiency by reducing waiting times and ensuring food availability, while also providing greater convenience for consumers. From the providers’ perspective, the pre-order system enables better production planning, accurate stock management, and reduced food waste. Furthermore, the findings highlight that PRO-KANTIN fosters entrepreneurial innovation by integrating digital technology with traditional service models, thereby creating new value for all stakeholders in the campus ecosystem. In conclusion, this research demonstrates that PRO-KANTIN is not merely a technical solution but also a strategic model that supports digital transformation, enhances entrepreneurial capacity, and strengthens the sustainability of campus-based entrepreneurial ecosystems. The implications suggest potential scalability to other institutions and communities, positioning PRO-KANTIN as a replicable model for digital entrepreneurship in higher education.